Accumulation of Social Capital as a Competitive Advantage of Companies which are Loyal to the Principles of Corporate Citizenship - Kuznetsova, Natalia Victorovna; Matveeva, Elena Vladimirovna (International Journal of Economics and Financial Issues, 2015)
This paper examines the characteristics that are peculiar to the corporate citizenship in the phase of maturity. The strategic forms of corporate citizenship that influence the productivity of the organization are explored. Modern business uses cause-related marketing and corporate social marketing as a strategic tool for sustainable development. The role of corporate citizenship and its interdependence with the sustainability of the organization is examined. The paper provides the evidence of interdependence between the sustainable development of the company and its accordance to the principles of the corporate citizenship. The mechanism of integration of principles of sustainable development on the basis of corporate citizenship activities is elaborated. The correlation between the corporate citizenship and accumulation of social capital is determined. Moreover, corporate citizenship is examined as an organization’s policy for overcoming crisis and managing the external environment. New forms of contemporary corporate citizenship are examined; those characteristics are distinguished that confirm corporate citizenship as the highest level of the corporate social responsibility. The paper includes the research of the companies that position themselves as corporate citizens and it confirms the correlation between the effectiveness of the management of the environment and the management of business built on the principles of corporate citizenship. The paper lists the activities needed to introduce the corporate citizenship in a company. Keywords: corporate social responsibility, corporate citizenship, globalization, think tank, social capital, human capital, public-private partnership, venture philanthropy. JEL Classifications: A13, D60, M14